DOES LEGAL TRANSPLANTATION WORK? THE CASE OF INDONESIAN CORPORATE GOVERNANCE REFORMS - Harijono, Harijono; Tanewski, George (Journal of Indonesian Economy and Business, 2012)
This study examines the impact of corporate governance reforms by analysing theÂ relation between firmsâ operating performance and key ownership structure and corporategovernance variables on a sample of firms listed on the Jakarta Stock Exchange betweenÂ the periods 1993 to 2007. Contrary to widespread belief that reforms in Indonesia havefailed, this paper provides empirical evidence in support of the positive impact ofÂ corporate governance reforms. While the impact of family control, the firmsâ businessÂ group affiliation, divergence between cash flow and control rights and political connectionÂ are all negatively associated with firmsâ operating performance (ROA) for the pre-reformperiod (i.e., 1993-1999), these negative effects disappear during the post-reform periodÂ (i.e., 2001-2007), except for family control. More importantly, the relationship betweenfamily control and operating performance is negative only when the familyâs control rightÂ exceeds their cash flow right. This study provides some empirical evidence and insights toboth regulators and development assistance agencies on the effectiveness of IndonesianÂ corporate governance reforms.Keywords: corporate governance reform, controlling shareholders, firm performance,Â Indonesia